Comparing low-dose (DART) and enhanced low-dose dexamethasone regimens in preterm infants with bronchopulmonary dysplasia - Al-taweel, Heba Mohamed; Abdelhady, Ismail Sabry Ismail; Irfan, Nasreen; Khzzam, Fadi Al; Kamal, Abdullah; Thazhe, Sudheer Babu Kurunthattil; Bayoumi, Mohammad A. A.; Gad, Ashraf (Frontiers in Pediatrics, 2023)
Introduction Determining the optimal dexamethasone dosage for facilitating extubation in extremely low birth weight (ELBW) infants with bronchopulmonary dysplasia (BPD) remains uncertain. This study aims to compare the effectiveness of low-dose (DART) and enhanced low-dose dexamethasone regimens in achieving successful extubation in these infants. Methods We conducted a retrospective cohort study at the Women's Wellness and Research Center (WWRC) involving ELBW infants who received dexamethasone for BPD prevention or treatment, or for extubation between January 1st, 2015, and December 31st, 2019. Our goal was to assess successful extubation within various time points of treatement. Results A total of 77 patients, matched in gestational age and BW, were enrolled in the study, receiving a total of 121 dexamethasone courses. Low-dose dexamethasone courses were administered 75 times to 49 infants, while 46 courses of enhanced low-dose were given to 28 infants. Treatment commenced at 30.8 ± 3.4 weeks post-menstrual age, compared to 32.1 ± 2.5 weeks in the enhanced low-dose group (p = 0.014). The median (IQR) course duration was seven (3–10) days in the low-dose group, while it was 10 (8–14) days in the enhanced low-dose group (p < 0.001). The median (IQR) course dose was 0.73 (0.53–0.86) mg/kg in the low-dose group and 1.27 (0.97–2.05) mg/kg in the enhanced low-dose group (p < 0.001). There were no differences in extubation success at any time point between the two groups at 72 h and seven days after treatment initiation, by course completion, and within seven days after treatment completion. However, regression analysis identified several predictors of successful extubation; baseline FiO2, course duration, and duration of invasive mechanical ventilation were negatively associated with successful extubation at various time points, while received dose per kg and cumulative dose positively correlated with successful extubation at different time points. No significant differences were observed in secondary outcomes, including death or BPD. Conclusion The choice between low-dose and enhanced low-dose dexamethasone regimens may not significantly impact extubation success. However, careful consideration of dosing, ventilation status, and treatment duration remains crucial in achieving successful extubation. This study highlights the need for personalized dexamethasone therapy in ELBW infants.